Social inequalities in oral health and in use of oral health care services among adolescents in Uganda - I. OKULLO, A. N. ÅSTRØM, & O. HAUGEJORDEN (Paediatric Dentistry, 2004)
The aim of this study was to describe clinical and self-perceived indicators of oral health status and the use of oral health care services by social and demographic characteristics.